Elevated serum immunoglobulin E level as a marker for progression of immunoglobulin A nephropathy - Ji-Hoon Lee; Shin Yeong Lee; Jin Sug Kim; Da Rae Kim; Su Woong Jung; Kyung Hwan Jeong; Tae Won Lee; Yoo Ho Lee; Yang Gyun Kim; Ju Young Moon; Sang Ho Lee; Chun Gyoo Ihm (Kidney Research and Clinical Practice, 2016)
Background: Immunoglobulin E (IgE) has traditionally been associated with anaphylaxis and atopic disease. Previous studies reported that serum IgE levels are elevated in nephrotic syndrome and suggested IgE levels as a prognostic indicator in glomerular diseases. The aim of this study was to explore the association between serum IgE levels and renal outcome in patients with immunoglobulin A nephropathy (IgAN). Methods: We included 117 patients with biopsy-proven IgAN. Renal progression was defined if a patient meets one of these criteria: (1) a negative value of delta estimated glomerular filtration rate (mL/min/1.73 m2/mo) or (2) a rise in serum creatinine to an absolute level of ≥ 1.3 mg/dL (male) or 1.2 mg/dL (female). We defined delta changes in serum creatinine, estimated glomerular filtration rate, and proteinuria as a difference of values during the follow-up period. Results: A total of 117 patients with IgAN were included. The serum IgE level was significantly high in the renal progressive group compared with the nonprogressive group. Sex and history of gross hematuria were significantly different between the high-IgE group and the low-IgE group. Regression analysis showed that a male sex, initial proteinuria, and change of proteinuria were significantly associated with serum IgE levels. Conclusion: The serum IgE level is potentially associated with disease progression and pathogenesis of IgAN.